(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Mindfulness is full of various techniques and practices that stimulate full attention in everyday life. Although it is recognized that being 100% present with mind and body in a situation is difficult, with the increase in the popularity of technological tools these problems grow. specifically in youth and students. For the students of the program, a bachelor’s degree in performing arts at the Antonio Nariño University, achieving absolute concentration to execute their acting activities in the theater class and coexistence can become a challenge. It is at this point where mindfulness, its techniques, elements and tools can be transformed beyond an experience in a workshop for two or three days and becoming a habit that drives a change that students need in the teaching processes, to obtain satisfactory results in the field of education.